About the sensorless movement speed control of mine electric locomotives - Синчук, Олег Николаевич; Гузов, Эдуард Семёнович; Синчук, Игорь Олегович; Дебелый, Владимир Леонидович; Дебелый, Леонид Леонидович (Eastern-European Journal of Enterprise Technologies, 2014)
Questions of the control of speed of the mine electric locomotives with the purpose of increase of traffic safety on the underground transport are considered in the article. Noted that the rate should limit on dangerous sections of the route. This requires effective and reliable speed control device. Analysis of existing speed, which uses relationship with the rotating elements of the traction electrotechnical transmission of electric locomotive is conducted. Peculiarities and deficiencies produced at the present time the speedometer with a Hall sensor, mounted at the gearbox electric locomotive. The analysis showed that produced the speed gauge is not able to ensure reliable operation, bringing most of the locomotives are operated without speed indicators. Authors proposed to ensure high reliability of the speedometer to apply sensorless speed control by using only the electric parameters of traction engines, such as rotor voltage and load current that uniquely identifies the speed. Calculation method for speed electro-mechanical characteristics with acceptable accuracy. Structural diagram of the speed gauge to measure and display the speed of the locomotive is given in the article. Sensorless the speed gauge is easier to manufacture and installation, maintenance, much more reliable, can reduce costs and increase the safety of operation of electric transport.